2015
DOI: 10.1002/tox.22210
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF administration attenuates brain injury in rats following carbon monoxide poisoning via different mechanisms

Abstract: Acute severe carbon monoxide (CO) poisoning induces hypoxia that leads to cardiovascular and nervous systems disturbances. Different complex mechanisms lead to CO neurotoxicity including lipid peroxidation, inflammatory and immune-mediated reactions, myelin degeneration and finally neuronal apoptosis and necrosis. Granulocyte colony-stimulating factor (G-CSF) is considered to be a novel neuroprotective agent. In this study, we evaluated the efficacy of G-CSF therapy on CO neurotoxicity in rats with acute CO po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Our previous study showed that RES could ameliorate CO‐induced cardiovascular effects in an animal model (Hashemzaei et al , ). In order to find new substances that can fight the deleterious effects of CO poisoning in the heart and brain and also to shed light on the underlying mechanisms, in our previous studies, we discussed the involved pathways (Ghorbani et al , ; Hashemzaei et al , ; Mohamadpour et al , ). To the best of our knowledge, it is for the first time that the neuroprotective effect of multiple‐dose RES administration on CO poisoning is evaluated in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that RES could ameliorate CO‐induced cardiovascular effects in an animal model (Hashemzaei et al , ). In order to find new substances that can fight the deleterious effects of CO poisoning in the heart and brain and also to shed light on the underlying mechanisms, in our previous studies, we discussed the involved pathways (Ghorbani et al , ; Hashemzaei et al , ; Mohamadpour et al , ). To the best of our knowledge, it is for the first time that the neuroprotective effect of multiple‐dose RES administration on CO poisoning is evaluated in rats.…”
Section: Introductionmentioning
confidence: 99%
“…CO poisoning is one of the most common clinical emergencies, and effective disease models are critical to the study of underlying mechanisms and developing novel therapeutic strategies. Numerous studies have adopted suction canisters to induce CO intoxication model . However, since the variability of animal activity resulted in various breathing rate, the exposure of CO among animals lacked comparability.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have adopted suction canisters to induce CO intoxication model. 41,42 However, since the variability of animal activity resulted in various breathing rate, the exposure of CO among animals lacked comparability. In this study, inspired by Fecther 43,44 who induced cochlea injury by means of CO injection ip, we used CO ip injection to establish acute CO poisoning model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CO exposure has been shown to cause lipid peroxygenation, (i.e. degradation of unsaturated fatty acids) leading to reversible demyelination of CNS lipids [22]. CO exposure also creates substantial oxidative stress on cells, with production of oxygen radicals resulting from the conversion of xanthine dehydrogenase to xanthine oxidase [23].…”
Section: Biochemistry Physiopathology and Pathologymentioning
confidence: 99%